THE MID - TERM EFFECT OF KINESIO TAPING ON PEAK POWER OF QUADRICEPS AND HAMSTRING MUSCLES AFTER ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION - Amel Khabazan Mahdi; Soltani Hossein (Physical Education of Students)
Purpose: The aim of this study was to assess mid- term effect of Kinesio tape on peak power of quadriceps and hamstrings muscles after ACL reconstruction 24 hours after taping. Material: Thirty six men who had undergone ACL reconstruction and completed physiotherapy periods (6 months) were assigned to no taping, placebo and taping groups. Peak power was tested before and 24 hours after taping by Isokinetic dynamometry. Data was analyzed by SPSS software 19. ANOVA and post hoc test (LSD) were used for interpretive analysis. Results: The results showed that the effect of Kinesio tape on peak power of quadriceps muscles at velocities of 180°/s and 300°/s was significant. In the hamstring muscles, significant effects were obtained at velocities of 60°/s, 180°/s & 300°/s. Conclusion: Positive impacts of Kinesio tape on muscular peak power among athletes who had ACL reconstruction were observed. Regardless of psychological effect and reducing re - injury fear, Kinesio - tape causes to stabilize and increase effective range of motion of the knee, so it is recommended that in the explosive training, athletes who have ACL reconstruction should use tape to reduce the probability of re-injury and increase muscle power.